Capturing Protein–Nucleic Acid Interactions by High‐Intensity Laser‐Induced Covalent Cross‐Linking†. (6th September 2022) - Angelov, Dimitar; Boopathi, Ramachandran; Lone, Imtiaz Nisar; Menoni, Hervé; Dimitrov, Stefan; Cadet, Jean
ABSTRACT: Interactions of DNA with structural proteins such as histones, regulatory proteins and enzymes play a crucial role in major cellular processes such as transcription, replication and repair. The in vivo mapping and characterization of the binding sites of the involved biomolecules are of primary importance for a better understanding of genomic deployment that is implicated in tissue and developmental stage‐specific gene expression regulation. The most powerful and commonly used approach to date is immunoprecipitation of chemically cross‐linked chromatin (XChIP) coupled with sequencing analysis (ChIP‐seq). While the resolution and the sensitivity of the high‐throughput sequencing techniques have been constantly improved, little progress has been achieved in the cross‐linking step. Because of its low efficiency, the use of the conventional UVC lamps remains very limited while the formaldehyde method was established as the "gold standard" cross‐linking agent. Efficient biphotonic cross‐linking of directly interacting nucleic acid–protein complexes by a single short UV laser pulse has been introduced as an innovative technique for overcoming limitations of conventionally used chemical and photochemical approaches. In this survey, the main available methods including the laser approach are critically reviewed for their ability to generate DNA–protein cross‐links in vitro model systems and cells. Abstract : Formaldehyde DNA–protein cross‐linking : protein–protein and DNA–protein XLs; capturing both direct and nondirect DNA–protein interactions; epitope loss; presence of artifacts DNA–protein interactions; ChIP‐grade antibodies required; suitable for Hi‐C and 3C genome conformation mapping; no special equipment required. Biphotonic UV laser DNA–protein cross‐linking : only DNA–protein XLs; capturing only direct DNA–protein interactions; no epitope loss; no ChIP‐grade antibodies required; no suitable for Hi‐C and 3C genome conformation mapping; special, noncommercially available, equipment needed.